Grinding enhances the magnetic hardness of heterometallic diruthenium(ii, iii) carbonates with a kagome lattice structure. Issue 47 (26th November 2020) - Feng, Li-Na; Tian, Yu-Chen; Li, Jing-Yu; Yang, Jian-Hui; Liu, Bin
Abstract : A manual grinding strategy promotes the magnetic hardness of Cs3 Cd(H2 O)6 [{Cd(H2 O)3 }2 {Ru2 (CO3 )4 }3 ]·10H2 O with a kagome lattice structure. Abstract : The assembly of paddle–wheel Ru2 building units affords a new trimetallic carbonate, Cs3 Cd(H2 O)6 [{Cd(H2 O)3 }2 {Ru2 (CO3 )4 }3 ]·10H2 O (1 ), that contains structurally near-perfect kagome layers, {Ru2 (CO3 )4 } n 3 n −, linked by octahedral Cd(H2 O)3 2+ into a nanoscale kagome network exhibiting ferromagnetic ordering below 3.5 K. The investigation of influences of the grinding method on the crystal samples of compound 1 reveals that the coercivity increases from ∼2.5 Oe to 44.0 Oe upon a grinding treatment for 180 minutes. The results demonstrate that compound 1 can vary from a soft magnet to a hard magnet simply by manually grinding the crystal samples to the nanoscale.